ICCREM 2018 Construction Enterprises and Project Management - Wang, Yaowu; Zhu, Yimin; Shen, Geoffrey Q.P; Al-Hussein, Mohamed (American Society of Civil Engineers, 2018)
Selected papers from the International Conference on Construction and Real Estate Management 2018, held in Charleston, South Carolina, August 9–10, 2018. Sponsored by the Modernization of Management Committee of the China Construction Industry Association and the Construction Institute of ASCE. This collection contains 37 peer-reviewed papers on construction enterprises and project management. Topics include: public-private partnerships; evaluation and assessment of construction projects; efficiency analysis; and risk-sharing in construction projects. These papers will be of interest to construction professionals, researchers, planners, contractors, and banking and government officials.